Adaptive finite-time synergetic control for flexible-joint robot manipulator with disturbance inputs - Nguyen, X. C.; Le, D. T. (Національний технічний університет "Харківський політехнічний інститут", 2025)
In this paper, the adaptive finite time controller is designed for flexible-joint manipulator (FJM) to stabilize oscillations and track the desired trajectory based on synergetic control theory (SCT) under disturbance inputs. The problem of the proposed work consists in the development of a mathematical model of the flexible joint while ignoring the nonlinear components of the actuator and synthesizing the control law that ensures the system stability within a settling time. The aim of this study is to use finite-time synergetic controller to ensure the reduction of system tracking error, avoid vibration and achieve steady state in a certain time period. An adaptive synergetic law is developed to solve the problem of uncertainty in the mathematical model of the actuator of FJM and input disturbances. Methodology. First, based on SCT the finite-time controller is constructed via the functional equation of the first manifold. The control law is designed to ensure the movement of the closed-loop system from an arbitrary initial state into the vicinity of the desired attractive invariant manifold, that is, the target attracting manifold. Secondly, to adjust the control law online, an adaptive law is developed to estimate the disturbance acting on the input. Then, the Lyapunov function is used to prove that the system can be stabilized in a sufficiently small neighborhood of the origin within finite time under input disturbances. Novelty. The implemented controller is effective in ensuring stability over a given time, minimizing the jitter problem while maintaining tracking accuracy and system robustness in the presence of input noise. Results. Numerical simulation and experimental results are presented to illustrate the effectiveness of the proposed method. The research directions of the model were determined for the subsequent implementation of the results in experimental samples.

У роботі розроблено адаптивний кінцевий регулятор часу для гнучкого шарнірного маніпулятора (FJM) для стабілізації коливань та відстеження бажаної траєкторії на основі синергетичної теорії управління (SCT) при вхідних збуреннях. Завдання пропонованої роботи полягає у розробці математичної моделі гнучкого шарніра з ігноруванням нелінійних складових приводу та синтез закону управління, що забезпечує стійкість системи протягом часу встановлення. Метою даного дослідження є використання кінцевочасного синергетичного регулятора для забезпечення зниження помилки відстеження системи, виключення вібрації та досягнення стійкого стану за певний проміжок часу. Розроблено адаптивний синергетичний закон для вирішення проблеми невизначеності в математичній моделі приводу FJMта вхідних збурень. Методологія. По-перше, на основі SCTбудується кінцевий регулятор часу за допомогою функціонального рівняння першого різноманіття. Закон управління розроблений для забезпечення переміщення замкнутої системи з довільного початкового стану в область бажаного притягуючого інваріантного різноманіття, тобто цільового різноманіття. По-друге, для налаштування закону управління в режимі онлайн розробляється адаптивний закон для оцінки обурення, що діє на вході. Потім за допомогою функціїЛяпунова доводиться, що система може бути стабілізована у досить малої околиці початку координат за кінцевий час при вхідних збуреннях. Новизна. Реалізований регулятор ефективний для забезпечення стійкості протягом заданого часу, мінімізуючи проблему коливань, зберігаючи точність відстеження та надійність системи за наявності вхідного шуму. Результати. Наведено чисельне моделювання та експериментальні результати для ілюстраціїефективності запропонованого методу. Визначено напрями досліджень моделі для подальшоїреалізаціїрезультатів у експериментальних зразках.
Keywords: flexible-joint manipulator; synergetic control theory; finite-time control; Lyapunov function; adaptive control; гнучко-шарнірний маніпулятор; синергетична теорія управління; кінцевий час управління; функція Ляпунова; адаптивне управління